Mortem - Quek, Kar Men (2017)
Mortem is a webcomic revolving around the journey of a girl with face blindness chasing Death for an answer. The idea came to me as I was thinking of “what ifs”. What if someone awakes in another world when she sleeps? What if you can capture a god? What if someone who sees faces as a blur recognises a face among the crowd? Imagination can be brought to life with different formats of art. The initial project idea was pitched for a film format with VFX elements. The change of format was largely due to the fact that VFX did not seem like a viable career option for me; I could not picture myself in that field. I took this FYP as an opportunity to do something that I’ve not done before to explore and learn something that I really want to.